The Impact of Financial Literacy, Inclusion, and Credit Access on MSME Performance - Nanda Cecharia; Cynthia Eka Violita; M. Mustaqim; Devika Cherly Putrihadiningrum (Journal of Educational Management Research, 2026)
This study aims to examine the influence of financial literacy, financial inclusion, and access to finance on MSME performance. The research employs a quantitative approach using a survey method with a structured questionnaire distributed to 91 MSME actors selected through random sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software to test the relationships among variables and evaluate the proposed hypotheses. The results reveal that financial inclusion and access to finance have a positive and significant effect on MSME performance. This indicates that broader access to formal financial services and easier access to external funding play an important role in improving business efficiency, productivity, and sustainability. In contrast, financial literacy does not show a significant effect on MSME performance, suggesting that financial knowledge alone is insufficient to enhance business outcomes without effective implementation and access to financial resources. The implications of this study highlight the importance of strengthening financial inclusion policies and improving financing accessibility for MSMEs. Financial institutions and policymakers should prioritize expanding access to financial services and supporting funding mechanisms rather than focusing solely on financial literacy programs. These findings contribute to a better understanding of the determinants of MSME performance and provide practical insights for improving business competitiveness and sustainability.